Night witches - Adlington, Lucy (London: Hodder Children's Books, 2013)
Rain Aranoza is a teenage bomber-pilot from Rodina, a nation of science and fact ruled by the all knowing Aura, where the belief in witches or any type of superstition is outlawed. Rain's regiment is made up of only teenage girls and their role is vital to the war effort against the Crux, a nation of faith and belief, where nature and God are celebrated and worshipped. But Rain is struggling with another battle. She's always had a sense that her nature is different from everyone else's, and that a dormant power threatens to burst out of her. When she encounters a young Scrutiner she falls in love with him, but is torn between what she has been taught is right, and what feels right. As her understanding of her latent power grows, the enemy threatens both her friends and her love. She can no longer ignore the power but she must choose how she uses it ... But what will she lose in the process?
Keywords: Young adult fiction